Quinolone-Induced Painful Peripheral Neuropathy: A Case Report and Literature Review - Leonel J. F. Estofan MD; Stanislav Naydin MD; Gediminas Gliebus MD (SAGE Publishing, 2018)
We present a case report of a 20-year-old male with diabetes mellitus type 1, who developed severe painful peripheral neuropathy while on the second of a 10-day course with levofloxacin for the treatment of epididymitis. The intensity of the pain rapidly reached scores of 10/10 in a numeric scale 0/10, and the patient was transferred to an inpatient pain unit where he was treated aggressively with minimal improvement. A skin biopsy revealed small fiber neuropathy. Then the patient was treated with intravenous immunoglobulin, which improved the pain. Now the patient is on outpatient intravenous immunoglobulin infusions bimonthly and making a slow recovery.